Whole Brain Teaching and Multi-Sensory Environments on Cognitive Science Development: Moderated by Children's Learning Preferences - Choirun Nisak Aulina; Siti Masitoh; Fajar Arianto (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aims to determine the impact of whole-brain learning and a multi-sensory environment on developing cognitive abilities in early childhood. Method: This research method uses a quantitative, quasi-experimental approach. The State University of Malang Laboratory Kindergarten's classes B and C served as the population for this study. The sample was determined by purposive sampling, so there were 60 children. We carried out the data collection process in this study using observation and closed interviews. We conducted observations to evaluate children's cognitive science abilities, encompassing information processing, intelligence, reasoning, language development, and memory. We used closed-ended interviews to measure the children's visual, audio, and kinesthetic learning styles. We processed the data using the SPSS 17.0 program, which included a validity test to determine the product moment, a reliability test with alpha Cronbach, a normality test with Kolmogorov-Smirnov, a homogeneity test with the Levene test, and hypothesis testing to test a two-way ANOVA. Results show a positive relationship between cognitive science development and learning preferences in children's learning styles, whether visual, audio, or kinesthetic. Novelty: This research can improve children's effective recall of information and open opportunities for more inclusive and adaptive learning according to each child's cognitive needs. Therefore, further research in this area has the potential to shape educational practices that are more effective in recognizing the development of cognitive science in children's learning.